Skutečnost a subjekt II. - Benyovszky, Ladislav (Lidé města, 2002)
The reflection is an immediate continuation of the study „Reality and subject." It thoroughly analyses individual structural aspects of Spinoza's concept of reality: substance-mode; freedom-necessity; God-attribute-final thing; the cause itself. On the strength of this it shows a transformation in the concept of an individual thing - its understanding from conatus as an inherent characteristic. It shows that it has thus prepared a way to a unified approach to the man as an acting individual. The paper leads to the reflection that Spinoza was the first to regard the man as a subject.